2014
DOI: 10.1590/0047-2085000000047
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy for anxiety disorders in children and adolescents: a systematic review of follow-up studies

Abstract: Objective To conduct a systematic review about the long-term response to cognitive-behavioral therapy (CBT) for anxiety disorders (ADs) in children and adolescents. Methods The PubMed and ISI Web of Science databases were consulted. Search in the databases was performed in November 2012 and included cohort studies after CBT for ADs in children and adolescents with a follow-up period over 12 months. Results A total of 10 papers met the inclusion criteria. The follow-up period ranged from 12 months to 13 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…In line with our findings, numerous studies [48,63–66] have shown that cognitive-behavioral intervention led to successful treatment of anxiety disorder in students. In addition, young people exposed to cognitive-behavioral approach have high quality of life with regard to health and wellbeing, as well as lower levels of anxiety.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our findings, numerous studies [48,63–66] have shown that cognitive-behavioral intervention led to successful treatment of anxiety disorder in students. In addition, young people exposed to cognitive-behavioral approach have high quality of life with regard to health and wellbeing, as well as lower levels of anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…These results supported the findings from earlier studies, which showed long-standing benefit of cognitive-behavioral intervention in maintaining of reduction in anxiety and depression. [4852]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed in the study that there was a continuous decline in the depressive mean scores of those in the intervention group over time. The present findings agreed with past studies which indicate that cognitive behavioural intervention has a long-lasting benefit in sustaining decreased depression (e.g., Barrett et al, 2001;Davis et al, 2014). The result of this study equally validated the earlier study which shows that cognitive behavioural intervention was highly effective when applied to assist some populations like the parents of children with Down syndrome (Greaves, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a diagnosis of social anxiety was associated with poorer outcome. Davis et al, 2014 [73] 10 follow up studies on CBT with anxiety With a follow up of over 12 months, the authors concluded that CBT was useful whether conducted individually or in a group format and whether it included the family or not. Kandasamy et al, 2019 [74] 60 children and adolescents aged 6-16 years with anxiety spectrum disorders They found that greater baseline severity and a diagnosis of social phobia had a poorer outcome at 24 weeks.…”
Section: Authormentioning
confidence: 99%